Composition, in vitro antioxidant and antimicrobial activities of essential oil and oleoresins obtained from black cumin seeds (Nigella sativa L.) - Singh, Sunita (2014)
Gas chromatography-mass spectrometry (GC-MS) analysis revealed the major components in black cumin essential oils which were thymoquinone (37.6%) followed by p-cymene (31.2%), alpha-thujene (5.6%), thymohydroquinone (3.4%), and longifolene (2.0%), whereas the oleoresins extracted in different solvents contain linoleic acid as amajor component.The antioxidant activity of essential oil and oleoresins was evaluated against linseed oil system at 200 ppm concentration by peroxide value, thiobarbituric acid value, ferric thiocyanate, ferrous ion chelating activity, and 1,1-diphenyl-2-picrylhydrazyl radical scavenging methods. The essential oil and ethyl acetate oleoresin were found to be better than synthetic antioxidants.The total phenol contents (gallic acid equivalents, mg GAE per g) in black cumin essential oil, ethyl acetate, ethanol, and n-hexane oleoresinswere calculated as 11.47±0.05, 10.88±0.9, 9.68 ± 0.06, and 8.33 ± 0.01, respectively, by Folin-Ciocalteaumethod. The essential oil showed up to 90%zone inhibition against Fusarium moniliforme in inverted petri plate method. Using agar well diffusion method for evaluating antibacterial activity, the essential oil was found to be highly effective against Gram-positive bacteria.